2020
DOI: 10.1111/imcb.12315
|View full text |Cite
|
Sign up to set email alerts
|

Plasmacytoid dendritic cells suppress Th2 responses induced by epicutaneous sensitization

Abstract: Epicutaneous (EC) sensitization with protein allergens is the most important sensitization route for atopic dermatitis. Plasmacytoid dendritic cells (pDCs) are characterized by massive secretion of interferon‐α (IFNα). B6 mice are T helper type 1 (Th1)‐prone and are representative of non‐atopic humans, whereas BALB/c mice are Th2‐prone and are representative of atopic humans. Here, we show that naïve BALB/c mice contain a greater number of nonactivated pDCs in peripheral lymph nodes (LNs) than do naïve B6 mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…reported that plasmacytoid DCs, mostly Langerin - DCs activated by TSLP, could induce the generation of Foxp3 + regulatory T cells, but did not induce a Th1/Th2 response. The latest study also confirmed that plasmacytoid DCs suppressed Th2 responses induced by epicutaneous sensitization, which was the most important sensitization route for AD ( 13 ). Dermal Langerin + DCs, a minor population of skin DCs, also expressed Langerin but were totally distinguished from epidemic Langerin + LCs.…”
Section: Introductionmentioning
confidence: 68%
“…reported that plasmacytoid DCs, mostly Langerin - DCs activated by TSLP, could induce the generation of Foxp3 + regulatory T cells, but did not induce a Th1/Th2 response. The latest study also confirmed that plasmacytoid DCs suppressed Th2 responses induced by epicutaneous sensitization, which was the most important sensitization route for AD ( 13 ). Dermal Langerin + DCs, a minor population of skin DCs, also expressed Langerin but were totally distinguished from epidemic Langerin + LCs.…”
Section: Introductionmentioning
confidence: 68%
“…pDCs produce high levels of IFN-ab (type I). This cytokine impairs Th2 responses by blocking the normal development of Th2 cells and production of Th2 cytokines (especially IL-5) (44,45). The reduction in circulating pDCs during active esophageal inflammation could be indicating migration of these cells to the inflamed tissue to control the inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] Previous studies have found a significant increase in pDCs and partially activated TLR signaling pathways (TLR7/ 9, IRAK1, IRF7) in psoriasis vulgaris lesions; 14 an increase in pDCs but inactivated TLR signaling pathways in verruca vulgaris (VV) lesions. 15 Lin et al 16 found that epidermal sensitizer protein allergen (EC) is the most essential sensitization pathway in atopic dermatitis. PDCs mediate the regulation of dermal dendritic cells (dDCs) via IFN-γ and reduces Th2 responses resulting from EC sensitization.…”
Section: Discussionmentioning
confidence: 99%